Pedological parameters for flow simulation in river basins - Moreira, Luana Lavagnoli; Schwamback, Dimaghi; Rigo, Daniel (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Hydrological models, such as Soil and Water Assessment Tools (SWAT), are powerful water resources management tool. However, its use depends on many input data, generally from international/national bases that do not represent the regional reality of a local study. Among the input data, pedological information at regional and local scale is considered the most critical to obtaining and handling, especially in developing regions such as Brazil, and its lack leads to uncertainties in its simulations. The present paper has the purpose of present required procedures in order to obtain the values of each pedological parameter required by the SWAT to estimate average flows in watersheds. Throughout this paper are listed the procedures to obtain the pedological parameters for each class of soil, and by following these steps, we identified the values for the classes present in the study area. The study is applied to the Jucu river basin, located in the state of Espírito Santo, and will serve as reference and database for further hydrological studies of the same region or others, instead of using values that are inconsistent with their locality.